The Influence of Social Media Marketing on Purchase Intent: The Role of Mediation Brand Image and Brand Trust on The Brand of Sunscreen - Valorie Yang Cen, Ronald; Nurlaela, Siti; Anindita, Rina; Baskara, Ika (Devotion : Journal of Research and Community Service, 2025)
The growing awareness of skin care has led to the rise of many sunscreen brands, especially in tropical countries like Indonesia, making it vital to understand factors affecting consumer purchase intent through digital marketing strategies. This research analyzes the influence of social media marketing on purchase intention, directly and through the mediating roles of brand image and brand trust. Using a quantitative method, an online questionnaire was distributed to 124 active TikTok users who had seen promotions of Unitary sunscreen on the platform. Data were analyzed using Partial Least Squares – Structural Equation Modeling (PLS–SEM) with SmartPLS4 software. Results show that social media marketing via TikTok significantly strengthens brand image and brand trust in Unitary sunscreen. Creative, consistent, and lifestyle-relevant promotions help form positive perceptions and increase consumer confidence in product quality, driving purchase intent. The findings also reveal that direct calls to purchase are less effective without a strong brand image and brand trust. Therefore, digital promotion success depends on the brand’s ability to build emotional connections with consumers. This research contributes theoretically to digital marketing literature and offers practical implications for skincare industry players aiming to design more effective and targeted promotional strategies. It underscores the critical role of social media marketing in shaping consumer behavior through brand image and brand trust, especially in competitive markets like sunscreen products.